AKUMULASI LOGAM Pb DI PERAIRAN SUNGAI SAIL DENGAN MENGGUNAKAN BIOAKUMULATOR ECENG GONDOK (Eichhornia crassipes) - Yuliati, Yuliati (Jurnal Perikanan dan Kelautan, 2010)
A study aims to understand the effectiveness of Eichhornia crassipes asbioaccumulator of Pb present in the Sail River water in Pekanbaru has beenconducted on May 2009. Water and Eichhornia samples were collected from 4sampling points that are distributed along the river. Parameters measured were Pbcontent in the water and in the Eichhornia samples, and also water qualityparameters such as temperature, brightness, dissolved oxygen and pH. Resultsshown that Pb content in the water ranged from 0.36-0.45 ppm, while in theEichhornia , they were 0.02-0.04 ppm (in the root), 0.01-0.03 ppm (in the trunk)and 0.02-0.03 ppm (in the leaf). Based on these results, it can be concluded thatthe Pb content in the water is higher than that of the Pb allowed to be in the water(PP 82, 2001)